Community-based postpartum contraceptive counselling in rural Nepal: a mixed-methods evaluation. Issue 2 (17th December 2020) - Wu, Wan-Ju; Tiwari, Aparna; Choudhury, Nandini; Basnett, Indira; Bhatt, Rita; Citrin, David; Halliday, Scott; Kunwar, Lal; Maru, Duncan; Nirola, Isha; Pandey, Sachit; Rayamazi, Hari Jung; et al.
Abstract: Unmet need for postpartum contraception in rural Nepal remains high and expanding access to sexual and reproductive healthcare is essential to achieving universal healthcare. We evaluated the impact of an integrated intervention that employed community health workers aided by mobile technology to deliver patient-centred, home-based antenatal and postnatal counselling on postpartum modern contraceptive use. This was a pre–post-intervention study in seven village wards in a single municipality in rural Nepal. The primary outcome was modern contraceptive use among recently postpartum women. We performed a multivariable logistic regression to examine contraceptive use among postpartum women pre- and one-year post-intervention. We conducted qualitative interviews to explore the implementation process. There were 445 postpartum women in the pre-intervention group and 508 in the post-intervention group. Modern contraceptive use increased from 29% pre-intervention to 46% post-intervention ( p < 0.0001). Adjusting for age, caste, and household expenditure, time since delivery and sex of child in the index pregnancy, postpartum women one-year post-intervention had twice the odds (OR 2.3; CI 1.7, 3.1; p < 0.0001) of using a modern contraceptive method as compared to pre-intervention. Factors at the individual, family, and systems level influenced women's contraceptive decisions. The intervention contributed to increasing contraceptive use through knowledge transfer, demand generation, referrals to healthcare facilities, and follow-up. A community-based, patient-centred contraceptive counselling intervention supported by mobile technology and integrated into longitudinal care delivered by community health workers appears to be an effective strategy for improving uptake of modern contraception among postpartum women in rural Nepal.